The Effectiveness of a Cognitive Behavioral Program in Reducing Psychological Stress Among 12th Grade Female Students - Sherwan, Bareen; Naamat, Arian Tatar (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2025)
This study aimed to examine the effectiveness of a cognitive-behavioral program in reducing psychological stress among 12th-grade science stream female students. The researcher adopted the experimental method using a sample of female students from secondary schools in the Faida area, Duhuk Governorate. The sample was divided into an experimental group that underwent the cognitive-behavioral program and a control group that received no intervention. The researcher formulated two main hypotheses: that there would be no significant differences between the experimental and control groups in stress reduction, and no significant differences between pre-test and post-test scores within the experimental group. The study relied on a psychological stress scale, and the cognitive-behavioral program was prepared by the researcher. The findings revealed significant differences between the experimental and control groups in favor of the experimental group, demonstrating reduced psychological stress levels. The results also showed a statistically significant difference between pre-test and post-test scores of the experimental group, confirming the effectiveness of the cognitive-behavioral program in reducing psychological stress among participants